Queuing with Impatient Customers and Ordered Service - Barrer, D. Y. (Operations Research, 1957)
Two types of customer behavior are considered: (1) if a customer is acquired for service before he has waited a time τ0, he remains in the queue until served irrespective of whether or not his total waiting time exceeds τ0. Only those customers who wait for a time τ0 without being acquired for service become “lost” customers, and (2) a customer whose total waiting time is τ0 becomes a lost customer irrespective of whether he is acquired for service or not.